2016
DOI: 10.1021/acs.joc.5b02794
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvation and Dynamics on the Mechanism and Kinetics of Nucleophilic Aromatic Substitution Reactions in Liquid Ammonia

Abstract: The role of the solvent and the influence of dynamics on the kinetics and mechanism of the SNAr reaction of several halonitrobenzenes in liquid ammonia, using both static calculations and dynamic ab initio molecular dynamics simulations, are investigated. A combination of metadynamics and committor analysis methods reveals how this reaction can change from a concerted, one-step mechanism in gas phase to a stepwise pathway, involving a metastable Meisenheimer complex, in liquid ammonia. This clearly establishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…Studies on the effect of ion-pairing, explicit hydration and solvent polarity on the fluorodechlorination reaction. Angewandte metadynamics and committor analysis methods have been studied by Moors et al [52] They found that for 4-nitrofluorobenzene (74), the reaction proceeded via ac oncerted mechanism in the gas phase via transition state 77,b ut via an intermediate Meisenheimer complex 83 in solution (Schemes 17 and 18). For4 -nitrochlorobenzene (75), the reaction proceeded via aconcerted mechanism via transition state 78 in both the gas phase and in solution, and for 2,4dinitrofluorobenzene (76), the reaction occurs via aM eisenheimer intermediate 79 in both solution and the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the effect of ion-pairing, explicit hydration and solvent polarity on the fluorodechlorination reaction. Angewandte metadynamics and committor analysis methods have been studied by Moors et al [52] They found that for 4-nitrofluorobenzene (74), the reaction proceeded via ac oncerted mechanism in the gas phase via transition state 77,b ut via an intermediate Meisenheimer complex 83 in solution (Schemes 17 and 18). For4 -nitrochlorobenzene (75), the reaction proceeded via aconcerted mechanism via transition state 78 in both the gas phase and in solution, and for 2,4dinitrofluorobenzene (76), the reaction occurs via aM eisenheimer intermediate 79 in both solution and the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of DFTMD is the uniform treatment of the entire system, which allows not only electronic polarization of the solvent and solute but also explicit interactions such as hydrogen bonds. Herein, we use such techniques, as they allow to sample the entire proton‐transfer process while taking the dynamic solvent environment into account …”
Section: Introductionmentioning
confidence: 99%
“…Herein, we use such techniques, as they allow to sample the entire proton-transfer process while taking the dynamic solvent environmentinto account. [36,37] Previously,w ew ere able to experimentally measuret he pK a values of ar ange of sulfonphthaleine dyes, forw hich the general structure is visualized in Figure 1. [38,39] The next step in designing dyes engineeredt owards specific applications,h owever,r equires at horough understanding of the molecular factors governing the pK a .Areliable procedure is needed to reacht his goal.…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 In recent studies, we have successfully used the MTD technique to estimate free energy surfaces in a variety of systems, including heterogeneous catalysis and reactions in solution. 35 37 Sampling is advanced by adding Gaussian potential hills along a limited number of carefully chosen collected variables during the simulation, effectively flattening the FES by filling low-energy regions. The FES is then calculated as the opposite of the summation of the Gaussian hills.…”
Section: Methodsmentioning
confidence: 99%